Genetic divergence among Dimorphandra spp. accessions using RAPD markers - Sudré, Cláudia Pombo; Rodrigues, Rosana; Gonçalves, Leandro Simões Azeredo; Martins, Ernane Ronie; Pereira, Messias Gonzaga; Santos, Marilene Hilma dos (Ciência rural, 2011)
The genus Dimorphandra has distinguish relevance considering either medicinal or biodiversity aspects because it includes two species that are economically important flavonoids sources for pharmachemical industry (D. mollis Benth. and D. gardneriana Tul.), and species endemic to Brazil, such as D. jorgei Silva and D. wilsonii Rizz., threatened by extinction. In order to evaluate variability among accessions of D. mollis (fava-d'anta), D. gardneriana and D. wilsonii, it was collected fruit from individual plants from three Brazilian states in a total of 57 accessions, which were analyzed with RAPD markers. It was used 20 seeds per progeny; the DNA was extracted from fully-formed young leaves, which were collected in bulk. The data were analyzed using a binary matrix, in which the score one represented presence of a band and zero, absence. The similarity matrix was developed by using the arithmetic complement of the Jaccard index, later grouped based on the Neighbor Joining algorithm. It was found considerable intra and inter specific variability in Dimorphandra spp., which were separated into four groups. Though genetic variability was found, the collecting trips showed that most of these areas are subject to loss of genetic resources of fava-d'anta due to the following factors: continuous anthropic activity, propensity for natural fires, and loss of natural seed dispersers (large fruit-eating mammals). Therefore, protections of these areas and ex situ conservation are essentials for the maintenance of genetic variability of these species. O gênero Dimorphandra tem grande relevância, sobretudo nos aspectos medicinais e de biodiversidade, por incluir duas espécies que são importantes economicamente como fontes de flavonoides para indústria farmacoquímica (D. mollis Benth. e D. gardneriana Tull.), e espécies endêmicas do Brasil, como a D. jorgei Silva e D. wilsonii Rizz., sendo esta ameaçada de extinção. Objetivando avaliar a variabilidade entre acessos de D. mollis, D. gardneriana e D. wilsonii, foram realizadas coletas de frutos separados por planta em três estados brasileiros em um total de 57 acessos que foram analisados por meio da técnica RAPD. Utilizaram-se vinte sementes por progênie e o DNA, extraído de folhas definitivas, jovens, e coletadas em bulk. Os dados foram analisados utilizando-se uma matriz de dados binários. Para formação da matriz de dissimilaridade, foi utilizado o complemento aritmético do Índice de Jaccard e posteriormente o agrupamento pelo algoritmo de Neighbor Joining. O estudo revelou que existe variabilidade entre e dentro das espécies de Dimorphandra spp., o qual formou quatro grupos. Apesar da variabilidade genética constatada, as expedições de coleta demonstraram que a maioria das áreas amostradas está sujeita a perdas de recursos genéticos de fava-d'anta devido aos seguintes fatores: ocorrência de ação antrópica contínua; propensão a incêndios naturais; e diminuição dos dispersores naturais de sementes (grandes mamíferos frugíveros). Assim, a proteção destas áreas e a conservação ex situ, são primordiais para manutenção da variabilidade genética dessas espécies.